Diagnóstico de reutilização e reciclagem de resíduos sólidos de construção civil pelas cooperativas de reciclagem no município de Belém-PA - ALMEIDA, Ana Victoria da Costa (Universidade Federal do Pará, 2019)
The Civil Construction sector is one of the most important segments of the world industry, being also the one that consumes the most natural resources, and therefore generates a large amount of solid waste. Construction Waste (RCC) is considered inert, but can cause problems when not properly disposed of. When we talk about RCC, we have CONAMA Resolution 307 stating that all municipalities must give RCC’s an environmentally sound destination in order to effectively reduce the environmental impacts generated by this type of waste. Within this context the present study made a diagnosis of the main practices involving reuse and recycling of RCC’s by recycling cooperatives in the city of Belém do Pará. To this end, an RSL was performed that assisted in the development of tools for the application of this research, and also helped in the conduction of studies that deal with the theme. With RSL it was possible to conclude that no study unites RCC’s and recycling cooperatives as a way of mitigation. Along with the cooperatives a Survey was applied and then a Likert scale through which it was found that the 4 cooperatives are already handling RCC’s and that it is no longer intense due to the lack of communication channel between the RCC generators and the cooperatives. Therefore, it is concluded that cooperatives are important allies for better management and destination of RCC’s and it is interesting to explore their potential, increasingly mitigating environmental problems related to the lack of RCC management by the municipality in question and thus give a more appropriate destination with help and social contribution for the cooperatives and the population of the municipality in question